Analisis Kecelakaan dan Biaya Kerugian Materil Jalan Lintas Banda Aceh – Medan STA 0 + 465 – STA 15 + 480 - Darmawan, Surya; Firdasari, Firdasari; Fahriana, Nina (Jurnal Talenta Sipil, 2024)
The purpose of this study is to determine accident-prone areas on the Banda Aceh – Medan Causeway, identify factors of traffic accident-prone areas that often occur on the Banda Aceh – Medan Causeway and also calculate the cost of material losses for the last four years, namely in 2018-2021. The methods used in this study are descriptive research types and quantitative approaches. The data analysis technique used is the UCL and AEK methods. The results obtained in this study are based on the Accident Equivalent Rate (AEK) method and the Upper Control Limit (UCL) method in 2018-2021, areas that are prone to accidents are located at STA 009 + STA 474 - STA 012 + STA 477, while at other STA locations below the UCL line or smaller than the UCL value, they are not at risk of being accident-prone. Based on the analysis of the factors causing areas prone to traffic accidents that often occur on the Banda Aceh – Medan STA 009 + 474 - STA 012 + 477 Causeway due to road condition factors, driver negligence factors and incomplete road facilities factors. And based on the calculation of material losses due to accidents on the Banda Aceh – Medan STA 0 + 465 – STA 15 + 480 Causeway, there are material losses of Rp. 19,755,323,448.31 during 2018-2021.